The four-story mistake - Enright, Elizabeth, 1909-1968 (Square Fish/Henry Holt and Co., 2008)
The Melendy family moves to a house in the country where a secret room, a cupola, a stable, and a book provide Mona, Rush, Randy, and Oliver with adventures far different from the city life to which they are accustomed.